Constraints and Strategic Suggestions for Enhancing Integrated Farming Systems among Bonda Tribal Family Farms - Suman, Swati; Deb, Atanu; Kumar Prusty, Ajay (Indian Journal of Extension Education, 2025)
Integrated Farming System (IFS) is a sustainable approach that improves productivity, resilience, and livelihoods, especially in tribal regions with limited resources and fragile environments. The study focused on the Bonda tribe, a Particularly Vulnerable Tribal Group (PVTG) in the Khairput block of Malkangiri district, Odisha, and identified the constraints faced by Bonda farmers in adopting IFS practices and suggestions for improvement. Six villages in Khairput block were selected using a simple random sampling method, with 25 respondents from each village, resulting in a total sample size of 150. Data were collected using a structured interview schedule. Garrett’s Ranking Technique was applied to rank key constraints, which were grouped into six categories. Content analysis was used to interpret the suggestions provided by the farmers. The main barriers included lack of training (64.57), resistance to change from traditional practices (64.56), and market inaccessibility (62.25). Farmers showed a willingness to adopt IFS if proper support was given. They recommended capacity building, livelihood diversification, better market access, and water and soil conservation strategies. The study emphasizes the need for culturally relevant and participatory IFS models to improve tribal farming systems.
Keywords: Bonda Tribe; Capacity Building; Food Security; Integrated Farming; Livelihood Diversification; Participatory Extension